FAKTOR-FAKTOR YANG MELATARBELAKANGI KERJASAMA EKONOMI DIGITAL INDONESIA-TIONGKOK TAHUN 2022-2023 - Dewi, Sari Amalia; Rayyis, Adryananta (Moestopo Journal of International Relations (MJIR), 2023)
This study analyzes the underlying factors that shaped the formation of digital economic cooperation between Indonesia and China during the period of 2022–2023, within the broader context of global digital transformation and evolving bilateral relations. Amid the rise of China as a digital power and Indonesia’s strategic efforts to modernize its economic infrastructure, digital cooperation has emerged as a pivotal component of both countries' foreign policy and economic agendas. The research adopts a qualitative explanatory method, using literature studies and documentary analysis to trace causal linkages between domestic drivers, foreign policy orientations, and structural factors in international cooperation. The theoretical framework integrates the concept of national interest, international cooperation theory, and digital economy strategy. Findings reveal that the convergence of Indonesia’s infrastructure priorities under President Joko Widodo and China's Digital Silk Road initiative created a conducive environment for bilateral digital partnership. Key enabling factors include aligned economic interests, regulatory openness, and the strategic use of digital diplomacy. The study concludes that digital cooperation reflects a pragmatic adaptation of Indonesia’s foreign policy to leverage economic opportunities while navigating the regional digital ecosystem shaped by China’s technological rise.